Morphological Status of Eight-Year-Old Girls of Varying Degrees of Nutritional Status - Đorđević, Marija M; Mitrović, Bojan J (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
Nutritional status of children is one of the most important indicators of health, mental and physical capabilities and potential for normal and healthy growth and development. The aim of this study was to determine differences in morphological characteristics in eight-year-old girls with varying degrees of nutritional status. The research was conducted on a sample of 91 second grade students of elementary schools in Niš, aged 8.06 (± 0.02). Based on the BMI, three sub-samples were formed (normal weight, overweight and obese subjects). Morphological status was determined by measuring the parameters of longitudinal, transversal and circular dimensionality, body weight and subcutaneous fatty tissue. Differences in morphological variables were determined by using MANOVA/ANOVA and LSD Post Hoc test. The results indicate that, in regards to the BMI, there are significant differences in morphological characteristics in eight-year-old girls. The highest values were observed in obese, then overweight, while the value for at least had a normal weight girls.